The real exchange rate and economic growth: Are developing countries different? - Martin Rapetti; Peter Skott; Arslan Razmi (University of Massachusetts, Department of Economics, 2011)
Recent research has found a positive relationship between real exchange rate (RER) undervaluation and economic growth. Different rationales for this association have been offered, but they all imply that the mechanisms involved should be stronger in developing countries. Rodrik (2008) explicitly analyzed and found evidence that the RER-growth relationship is more prevalent in developing countries. We show that his finding is very sensitive to the criterion used to divide the sample between developed and developing countries. We then use alternative classification criteria and empirical strategies to evaluate the existence of asymmetries between groups of countries and find that the effect of currency undervaluation on growth is indeed larger and more robust for developing economies. However, the relationship between RER undervaluation and per capita GDP is non-monotonic.
Keywords: F43; O11; 330